Development of Interactive Multimedia Based on ISpring Suite with Corrective Feedback to Improve Student’s Conceptual Understanding Ability - Fajar Kurnia Awala; Yesi Franita; Zuida Ratih Hendrastuti (Pendidikan Matematika UNIMOR, 2024)
The ability to understand mathematical concepts are one of the abilities that must be achieved. Based on the results of the initial test, the conceptual understanding ability of class IX students at one of schools in Magelang are relatively low. The aim of this research was to produce iSpring Suite-based learning multimedia products with valid, practical and effective corrective feedback in improving students' concept understanding abilities. The research belongs to research and development using the Borg and Gall model. The results of the validity test were 88.44% by material experts in the